The Sunland Training Centers: Florida's Institutes for Children with Intellectual Disabilities - Kim Curry (University of North Florida, 2013)
Developmental disabilities affect about one out of every six children in the United States. These conditions create significant financial and social costs to families and society. Specifically, questions have long arisen as to how best to manage the needs of persons with intellectual disabilities. Historically, the nomenclature used to address intellectual disabilities has evolved as has the philosophy of venues to provide optimal care and the development of specific skills for conducting this care. Considerable dissension still exists about the type and nature of institutional care for even the most profoundly disabled individuals. This paper reviews relevant history, including laws, regulatory measures, and landmark judicial decisions with a special focus on Florida.